Annotated Listing of New Books (Journal of Economic Literature, 2018)
Editor's Note Our policy is to annotate all English-language books on economics and related subjects that are sent to us. A very small number of foreign-language books are called to our attention and annotated by our consulting editors or others. Our staff does not monitor and order books published; therefore, if an annotation of a book does not appear six months after the publication date, please write to us or the publisher concerning the book.